Neurosurgery and Medical Management of Severe Head Injury. (5th September 2018) - McCafferty, Randall R; Neal, Chris J; Marshall, Scott A; Pamplin, Jeremy C; Rivet, Dennis; Hood, Brian J; Cooper, Patrick B; Stockinger, Zsolt
Abstract: Management of the patient with moderate to severe brain injury in any environment can be time consuming and resource intensive. In the austere or hostile environment, the challenges to deliver care to this patient population are magnified. These guidelines have been developed by acknowledging commonly recognized recommendations for neurosurgical and neuro-critical care patients and augmenting those evaluations and interventions based on the experience of neurosurgeons, trauma surgeons, and intensivists who have delivered care during recent coalition conflicts.